The impact of technology, learning style, instructional approach, and attitude on learning outcomes - Hala, Majlinda; Xhomara, Nazmi (International Journal of Evaluation and Research in Education (IJERE), 2024)
The study aims to investigate the relationship between the learners’ technology experiences, cooperative learning style, student-centered instructional approach, and positive student attitude toward learning outcomes. Quantitative correlation model, a semi-structured instrument, and a cluster random sample of subjects (N=319) were decided to be employed in the research-study. The study reported a relatively low positive relation between learners’ technology experiences and learning outcomes variables (r=.328), an intermediate positive connection between cooperative learning style and learning outcomes constructs (r=.485), a relatively low positive association in the middle of student-centered instructional approach and learning outcomes (r=.394), as well as between positive student attitude and learning outcomes (r=.329). The whole variance of learning outcome levels described by cooperative learning style is 34.7%, by student-centered instructional approach is 23.9%, by positive student attitude is 10.8%, and by learners’ technology experiences is 5.6%. The results of the study are important for departments as well as for lecturers and students.